La sociologia visuale contemporanea. Un approccio introduttivo - Ciampi, Marina (SocietàMutamentoPolitica, 2016)
The author opens the essay with a preliminary discussion on the identity and the main application fields of visual sociology: in the first part she analyzes the thought of those sociologists who marked the relationship between sociological research and photographic images. The second part is devoted to those contributions that gave rise to the methodological debate on the use of audio-visual instruments: the author intervenes explaining the need to constantly refer to the epistemic dimension, thus ensuring a full procedural and scientific rigor for visual sociology.